1987
DOI: 10.1557/proc-96-321
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects in Rare-Earth Permanent Magnets

Abstract: Nd-Fe-B and Sm-Co permanent magnets have been irradiated with fission neutrons and gamma rays. Irradiated samples were periodically removed for room temperature measurements of the open-circuit remanence. Hysteresis loops were measured before and after irradiation. For neutron irradiation, two Nd-Fe-B magnets showed a rapid loss of remanence, while a third magnet from another manufacturer decayed more slowly, suggesting that the radiation hardness of Nd-Fe-B magnets may depend on microstructural details. Irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Many researches have studied the radiation-induced effects on such materials and facilities with ion beams [18], protons [19], and high-energy neutrons [20] and ␥-ray [21]. Gamma-ray irradiation is known to generate controlled defects of various types such as point, cluster, and columnar defects in the materials [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have studied the radiation-induced effects on such materials and facilities with ion beams [18], protons [19], and high-energy neutrons [20] and ␥-ray [21]. Gamma-ray irradiation is known to generate controlled defects of various types such as point, cluster, and columnar defects in the materials [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…With performance tests under the hightemperature and high-pressure water, it can be concluded as follows. 11) These data can lead that the effect of radioactive rays on the material in the present INV-CRDM for MRX is very small. Therefore, it does not need any special measure for irradiation of the materials.…”
Section: Discussionmentioning
confidence: 77%
“…Irradiations performed by Cost et al 19 have shown that SmCo magnets had good radiation resistance even at 10 18 n/cm 2 , while NdFeB magnets showed significant degradation at 10 15 n/cm 2 and 10 16 n/cm 2 . However, they also showed that a certain type of NdFeB had significantly higher resistance than the rest though still worse than the SmCo samples.…”
Section: Neutron Irradiationmentioning
confidence: 99%